2018
DOI: 10.1080/01658107.2017.1420084
|View full text |Cite
|
Sign up to set email alerts
|

Photo Essay: Retinal Changes in Type 3 Gaucher Disease

Abstract: Ocular features of Gaucher disease include gaze abnormalities, corneal clouding, ocular deposits and pigmentary changes in the macula. We report the presence of bilateral fovea sparing macular deposits in a 21-year-old woman with type 3 Gaucher disease. Macular deposits occur due to glucocerebroside accumulation within histiocytes and retinal deposits might correlate with the degree of systemic infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
2
1
0
Order By: Relevance
“…[1][2][3] The hypopigmented spots correlated with preretinal hyperreflective bodies seen on optical coherence tomography (Figure, B), likely representing glycolipid deposits. 4 Although similar findings have been previously documented, 5,6 this patient had an ultrawidefield fundus appearance with accompanying ocular coherence tomography scan showing more extensive deposits.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…[1][2][3] The hypopigmented spots correlated with preretinal hyperreflective bodies seen on optical coherence tomography (Figure, B), likely representing glycolipid deposits. 4 Although similar findings have been previously documented, 5,6 this patient had an ultrawidefield fundus appearance with accompanying ocular coherence tomography scan showing more extensive deposits.…”
supporting
confidence: 83%
“…It has been suggested that the observed vitreous opacities represent Gaucher cells, which are enlarged glucocerebroside-filled histiocytes capable of crossing the blood-ocular barrier . The hypopigmented spots correlated with preretinal hyperreflective bodies seen on optical coherence tomography (Figure, B), likely representing glycolipid deposits . Although similar findings have been previously documented, this patient had an ultra-widefield fundus appearance with accompanying ocular coherence tomography scan showing more extensive deposits.…”
supporting
confidence: 80%
“…The prevalence of posterior segment abnormalities in Gaucher type 3 is not yet established. Recent case reports describe preretinal accumulations of matter [2024]. In fact, they even may promote severe tractive retinal detachment in Gaucher type 3 [25, 26].…”
Section: Introductionmentioning
confidence: 99%